Rudolf Steiner in the educational and cultural space. - Ionova O.M (Kharkov National Pedagogical University, 2011)
It is analyzed the life and career of R. Steiner, the author of important works on philosophy, epistemology; founder of the spiritual and scientific Humanities (anthroposophy) as the foundation for the development of different areas of knowledge and human activities (medicine, pharmacy, medical pedagogy, architecture, sociology, ecological agriculture, theater, etc.). Particular attention is given to translate the anthroposophic pulses in education - the basement and development of the Waldorf kindergartens and schools.